J-matrix calculation of electron-helium S-wave scattering - Konovalov, D.; Fursa, Dmitry; Bray, Igor (American Physical Society, 2011)
The J-matrix approach to electron-atom scattering is revised by merging it with the Fano's multiconfiguration interaction matrix elements [U. Fano Phys. Rev. 140 A67 (1965)]. The revised method is then applied to the S-wave model of the e-He scattering problem demonstrating remarkable computational efficiency and accuracy. In particular, the method is in complete agreement with the convergent-close-coupling elastic, 21,3S excitation and single ionization cross sections for impact energies in the range 0.1–1000 eV. The S-wave resonance structures in the elastic and 21,3S excitation cross sections are highlighted.